French security experts identify Moscow-based disinformation network - Willsher, Kim; O'Carroll, Lisa (The Guardian, 2024)
Network operating in western Europe is ‘paving way for new wave of online manipulation’ in crucial election year, French agency says
Keywords: Cyberwar; Europe; European Union; France; Internet; Russia; Technology; Ukraine; United Nations; World news

French security experts identify Moscow-based disinformation network - Willsher, Kim; O'Carroll, Lisa (The Guardian, 2024)
Network operating in western Europe is ‘paving way for new wave of online manipulation’ in crucial election year.
Keywords: Cyberwar; Europe; European Union; France; Internet; Russia; Technology; Ukraine; United Nations; World news